Self-Repairable Silicon Anodes Using a Multifunctional Binder for High-Performance Lithium-Ion Batteries - Malik, Yoga Trianzar; Shin, Seo-Yeon; Jang, Jin Il; Kim, Hyung Min; Cho, Sangho; Do, Young Rag; Jeon, Ju-Won (Wiley - V C H Verlag GmbbH & Co., 2023)
Despite of extremely high theoretical capacity of Si (3579 mAh g(-1)), Si anodes suffer from pulverization and delamination of the electrodes induced by large volume change during charge/discharge cycles. To address those issues, herein, self-healable and highly stretchable multifunctional binders, polydioxythiophene:polyacrylic acid:phytic acid (PEDOT:PAA: PA, PDPP) that provide Si anodes with self-healability and excellent structural integrity is designed. By utilizing the self-healing binder, Si anodes self-repair cracks and damages of Si anodes generated during cycling. For the first time, it is demonstrated that Si anodes autonomously self-heal artificially created cracks in electrolytes under practical battery operating conditions. Consequently, this self-healable Si anode can still deliver a reversible capacity of 2312 mAh g(-1) after 100 cycles with remarkable initial Coulombic efficiency of 94%, which is superior to other reported Si anodes. Moreover, the self-healing binder possesses enhanced Li-ion diffusivity with additional electronic conductivity, providing excellent rate capability with a capacity of 2084 mAh g(-1) at a very high C-rate of 5 C.